Students with disabilities’ experience in South African higher education – a synthesis of literature - Mutanga, O. (South African Journal of Higher Education, 2017)
This state of the art review paper offers a synthesis of published studies on students with disabilities’ experience in South African higher education since 1994, when a democratically elected government came to office. The article presents a review of published studies describing the experiences of students with disabilities in South African higher education (SAHE) in the period 1994-2017. In order to obtain a perspective on the experiences of students with disabilities in South African higher education institutions, a synthesis of the findings and implications of South African studies relating to students with disabilities in SAHE is provided. Three aspects will be discussed namely: (a) conceptualisation of disability; (b) access, inclusion and participation in higher education; and (c) supporting mechanisms for students with disabilities. From this, challenges, areas needing further studies, lessons learnt, approaches and policy implications for policy-practitioners and institutions are suggested.